Communication Ability and Related Factors in Children with Hearing Aids - doloksaribu, rico; -, Wijana (Oto Rhino Laryngologica Indonesiana, 2019)
Background : Hearing function is very influential on the development of speech and language. Hearing disorders in children can lead to disrupt of communication skills. Hearing aids help provide the development of the ability to hear, talk, and communicate. Some factors such as age, duration of use of hearing aids, and parental activeness in encouraging children to communicate and perform auditory verbal therapy are known have an effect on communication skills.Aim : Knowing the capabilities and related factors of communication  after using of hearing aids in children.Method : Had been done cross sectional study design at the private hearing centre in Bandung in the period January - May 2018. Inclusion criteria for this research is children who use hearing aids which control in the period January-May 2018Result : From  60 subjects that fit with research criteria. There were 35 childrens (58,33%)  who use mix communication, there were 23 childrens (38,33%) in special school. There were 37 childrens (61,67%) who have communication duration more than 6 hours. There were 45 childrens (75%) had routine  frequency of therapy. There were 23 childrens (38,33%) who use AVT&Speech Therapy. A total of 66.67% of subjects had a low PEACH score (< 60), 16.67% had a moderate PEACH score (> 60 - ≤ 75), and 16.66% had a normal PEACH score (> 75). The PEACH score in this study shows an average value of 52.63% with 16.66% had a normal PEACH score (> 75)Conclusion : Caractheristic that have a significant relationship with normal peach score, communication method, educational method, communication duration, frequency of therapy, and type of therapy used (p <0.05 )